The Human Side of Organizational Restructuring *) - Dr. Achmad Sobirin; Al Hasin, MBA; Trias Setiawati, Msi (Faculty of Psychology Universitas Gadjah Mada, 2005)
Under the new law and regulations, private higher education institutions(PTS in Indonesian term) are now given ample opportunities to manage their own institutions without necessary intervention from Directorate General of Higher Education (DGHE). With greater freedom from DGHE control, Universitas Islam Indonesia (best known as UII) inits effort to improve performance, has decided to redesign its organization, arguing that the existing design does not fit with the changing environment.